Facing wicked problems during a pandemic and beyond: A case study in using design thinking for CTL development and growth - Devon Moore; Jenna Pack Sheffield (To Improve the Academy, 2023)
In this article, the authors share the challenges we faced as we launched a center for teaching and learning during the COVID-19 pandemic, and we describe how we used design thinking as a strategy for working through these challenges. The article presents an overview of the design thinking process, a case study of our application of the process, and recommendations for how educational developers can leverage design thinking as a strategy for solving problems related to limited resources and low faculty engagement.